2008
DOI: 10.1093/jac/dkn402
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent antifungal activity against Aspergillus fumigatus developing multicellular filamentous biofilms

Abstract: Overall, the data presented demonstrate that treatment of actively growing A. fumigatus cells with antifungal agents is more efficacious than treating mature structures in vitro. Amphotericin B was consistently more effective against each phase and displayed rapid effects, and therefore may be a suitable option for managing patient groups at risk from aspergillosis infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
102
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 8 publications
12
102
2
1
Order By: Relevance
“…However, Ͼ95% of the reduction in metabolic activity was obtained with Af293 at the highest concentrations (32 g/ml for AMB and 16 g/ml for LAMB), and there was still 10% activity 24 h after challenging CG261 with 32 g/ml of both AMB and LAMB ( Fig. 1 and 2), in agreement with previous studies (6,13,18). Conversely, AlgL did not affect the time-kill curve of A. fumigatus Af293 and CG261 biofilms challenged with 1 U/ml of the compound, while a minimal reduction in metabolic activity over the 24-h period was shown following exposure to 10 U/ml AlgL, with a maximal 26% metabolism reduction displayed after 24 h ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, Ͼ95% of the reduction in metabolic activity was obtained with Af293 at the highest concentrations (32 g/ml for AMB and 16 g/ml for LAMB), and there was still 10% activity 24 h after challenging CG261 with 32 g/ml of both AMB and LAMB ( Fig. 1 and 2), in agreement with previous studies (6,13,18). Conversely, AlgL did not affect the time-kill curve of A. fumigatus Af293 and CG261 biofilms challenged with 1 U/ml of the compound, while a minimal reduction in metabolic activity over the 24-h period was shown following exposure to 10 U/ml AlgL, with a maximal 26% metabolism reduction displayed after 24 h ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11). Recent observations have consistently shown that all antifungal drugs are significantly less effective when A. fumigatus is grown as a biofilm than when it is grown in the planktonic state (4,7,9,12,13), presumably as a reflection of multiple resistance mechanisms, including the ECM, which would prevent drug diffusion by acting as a physical barrier (14). This could contribute to the overall mortality with invasive aspergillosis, which remains high, despite the use of newer broad-spectrum antifungal agents and diagnostic adjuncts (15).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…The Pel polysaccharide enhances resistance to several antibiotics including aminoglycosides and colistin (22,24,25). Because biofilm formation by A. fumigatus is associated with increased resistance to a number of antifungal agents (26)(27)(28), we hypothesized that GAG may have an analogous function to Pel in enhancing resistance to antifungal agents. To test this hypothesis, we investigated whether Sph3 h or PelA h could potentiate the activity of commonly used antifungal drugs.…”
Section: Sph3 H and Pela H Potentiate Antifungals By Enhancing Their mentioning
confidence: 99%